Measuring N2- Fixation by some Varieties of Groundnut and their Residual Effect on Subsequent Sorghum Crop using 15N Methodology - A.M. Adlan, Mohamed; O. Mukhtar, Nuri (Gezira Journal of Agricultural Science; Vol 1 No 1 (2003), 2021)
Five varieties of groundnuts were studied for their exact amount of nitrogen fixation effect on subsequent sorghum crop. The 15 N methodology was used with a non-nodulating groundnut isoline as the reference crop. Six months after the groundnut harvest, sorghum was sown to study the presence of any residual N from fixation and/or soils own conserved N. The non-nodulating groundnut as a reference crop could detect N fixation (Ndfa) as amounting to 60% —70% of the crops need, i.e., 20%-30% more than the 40% -50% detected using sesame as the reference crop. The N derived from soil (Ndfs) was reduced from 50%-60% to 30%-40% which is much closer to what the low N (300ppm) Gezira soil can provide. Subsequent sorghum was positively affected by the preceding groundnut varieties but only variety Medani gave significant straw and total biological yields over the non-nodulating isoline. There was, therefore, an indication of residual N represented by the higher parameters recorded for the varieties. Groundnut is thus a good preceding crop for cereals though more research work is needed in the area of biological nitrogen fixation.